2014
DOI: 10.1177/1357034x13520331
|View full text |Cite
|
Sign up to set email alerts
|

Risky Bodies in the Plasma Bioeconomy

Abstract: In 2003 the UK National Blood Service introduced a policy of ‘male donor preference’ which involved women’s plasma being discarded following blood collection. The policy was based on the view that data relating to the incidence of Transfusion-Related Acute Lung Injury (TRALI) was linked to transfusion with women’s plasma. While appearing to treat female donors as equal to male donors, exclusion criteria operate after donation at the stage of processing blood, thus perpetuating myths of universality even though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Despite commonly held beliefs that voluntary, unremunerated national blood services were founded on a social contract that binds communities together through appeals to universality and social citizenship, blood donation is a highly politicised issue. Within transfusion science we found that ‘gendered bodies are both naturalised and made invisible in a discourse which relies heavily on universalising myths that seek to value blood and plasma donation as a social and public good, and ties donation to citizenship and solidarity’ purporting that all donations are valued equally (Kent and Farrell ). Rather, through the practices of categorising, sorting, screening, testing and matching, transfusion science (like transplantation science) produces difference.…”
Section: Gender Dynamics Of Blood Cord Blood Placenta Foetal Tissumentioning
confidence: 99%
See 4 more Smart Citations
“…Despite commonly held beliefs that voluntary, unremunerated national blood services were founded on a social contract that binds communities together through appeals to universality and social citizenship, blood donation is a highly politicised issue. Within transfusion science we found that ‘gendered bodies are both naturalised and made invisible in a discourse which relies heavily on universalising myths that seek to value blood and plasma donation as a social and public good, and ties donation to citizenship and solidarity’ purporting that all donations are valued equally (Kent and Farrell ). Rather, through the practices of categorising, sorting, screening, testing and matching, transfusion science (like transplantation science) produces difference.…”
Section: Gender Dynamics Of Blood Cord Blood Placenta Foetal Tissumentioning
confidence: 99%
“…Women are given anti‐D when they do not need it because there are institutional priorities saying it is too difficult to distinguish between women who need it and women who do not. Women are put at risk because it is more ‘efficient’ to give this blood product to all women, regardless of whether they need it (which could be determined by foetal genotyping) (Kent and Farrell , Kent et al . ).…”
Section: Gender Dynamics Of Blood Cord Blood Placenta Foetal Tissumentioning
confidence: 99%
See 3 more Smart Citations